Effects of fresh, aged and cooked garlic extracts on short- and long-term memory in diabetic rats - Alireza Sarkaki; Saeed Valipour Chehardacheric; Yaghoub Farbood; Seyed Mohammad Taghi Mansouri; Bahareh Naghizadeh; Effat Basirian (Mashhad University of Medical Sciences, 2012)
Objective: The present study was hypothesized to investigate the beneficial effects of fresh, aged, and cooked garlic extracts on blood glucose and memory of diabetic rats induced by streptozocine (STZ). Material and Methods: Diabetes was induced by an intraperitoneal injection of STZ (60 mg/kg body weight). An oral dose of 1000 mg/kg of each garlic extract was given daily for 4 weeks after diabetes induction. Five days after STZ injection, five groups were formed: Control (intact) rats (Cont) + Vehicle of garlic extract (normal saline) (Veh), STZ + Veh, STZ + Fresh (row) garlic (FG), STZ + Aged garlic (AG), and STZ + cooked (boiled) garlic (CG). In order to assess the passive avoidance memory, rats were gently placed on the wooden platform, and latency to step-down (SDL) was recorded as initial phase, after then a light electrical shock [0.3 mA, 3 sec, Alternative current (AC)] was delivered to their foot paw. The retrieval tests were done for short- and long-term memories, respectively. Blood glucose was assayed by glucometer before and after treatment with STZ and garlic extracts. Results: Hyperglycemia induced by STZ decreased short-term memory in both diabetic males and females rats significantly compared with the controls (p